Clearance measurement for concrete waste generated by the decommissioning of uranium processing facilities. (15th September 2022) - Yokoyama, Kaoru; Ohashi, Yusuke
Highlights: Measurement tests for concrete waste were conducted using clearance verification system. Since the peaks of Ac-228, Tl-208, and K-40 are derived from concrete waste, the 1.001 MeV gamma rays emitted by 234m Pa ( 238 U decay-series) and the associated scattered gamma rays were used to determine uranium after correcting the gamma rays from concrete waste. When measuring about 300 kg of homogeneous concrete, which reflects the actual waste at the uranium processing facility, if the weight of uranium is 3 g or more, it can be quantified within a relative error of about 30%. Abstract: Decommissioning is planned at nuclear facilities that have been discontinued. We examined the evaluation method of uranium radioactivity for concrete waste generated by the decommissioning of nuclear facilities. Since the peaks of Ac-228, Tl-208, and K- 40 are derived from concrete waste, it is difficult to distinguish the 1001 keV peak emitted from the uranium source. We have derived a formula to correct gamma rays from concrete and the environment, and the amount of uranium was quantified. When the weight of concrete waste is about 300 kg, if the weight of uranium is 3 g or more, it can be quantified within a relative error of about 30%. Measurement tests were performed using homogeneous simulated concrete waste. Since uranium contamination is on the concrete surface at the uranium processing facility and small chunks generated by scraping the concrete surface will be stored in a drum and measured, it seems that the test of homogeneous concrete reflects the actual waste.